Vrstna sestava ektomikoriznih talnih združb bukovih sestojev različno onesnaženih gozdnih ploskev - Al Sayegh-Petkovšek, Samar (Zbornik gozdarstva in lesarstva, 2005)
Belowground ectomycorrhizal fungal communities at fagus stands were analysed. Eectomycorrhiza types were identified in soil cores from differently polluted beech forest research plots in the 1998 - 2001 period by mycobioindication method. Forest research plots were situated in the vicinity of thermal power plants (polluted plots: Zavodnje - Prednji vrh and Zasavje - Dobovec) and in unpolluted areas (in the vicinity of Kočevska Reka: Preža and Moravške gredice). Eighty-eight different ectomycorrhiza types were determined from a total of 95,044 root tips. Among them, 48 were identified down to the species level and 18 to the genus level; for 22 of them, no similarity was found with any of the already described types, so the majority of them are probably undescribed types. Short descriptions of 31 ectomycorrhiza types (most of themare undescribed types) are presented in this article. However, there are differences in species diversity of the types. Among the identified types of ectomycorrhizae, the dominant and common species were selected, some of which are probably the key species of belowground ectomycorrhizal communities of beech forests.
Keywords: biodiverziteta; bukov gozd; ektomikoriza; Fagus sylvatica; gozdna tla